Did remittance inflow in Bangladesh follow the gravity path during COVID-19? - Gour G. Goswami; Munim Kumar Barai; Mahnaz Aftabi Atique; Mostafizur Rahman (Economies, 2023)
Remittances are one of the major driving forces of economic growth in Bangladesh. The paper's main objective is to empirically investigate the effect of COVID-19 on the remittance inflow to Bangladesh using a gravity model framework. We have employed monthly data of remittance inflow to Bangladesh from January 2018 to September 2022 with its top twelve partners, namely the Kingdom of Saudi Arabia, the United Arab Emirates, Kuwait, Qatar, Oman, Bahrain, Libya, the United Kingdom, Italy, Malaysia, Singapore, and Japan. Using the gravity equation, we tapped the COVID-19 dummy as the critical variable of our interest, along with COVID transmission, mortality, and vaccination data at home and abroad. Using Poisson pseudo-maximum likelihood (PPML), fixed-effect (FE), and random-effect (RE) estimations, we find that during the COVID-19 pandemic, remittance inflow to Bangladesh increased significantly after controlling for other Gravity variables.
Keywords: 330; COVID-19; gravity model; remittance inflow; Bangladesh; panel data; South Asia